Kinome rewiring during acquired drug resistance in neuroendocrine neoplasms. Issue 1 (January 2021) - Gérard, Corinne; Lagarde, Marie; Poizat, Flora; Oziel-Taieb, Sandrine; Garcia, Vincent; Roche, Catherine; Niccoli, Patricia; Barlier, Anne; Romano, David
Abstract : Although there is evidence of a significant rise of neuroendocrine neoplasms (NENs) incidence, current treatments are largely insufficient due to somewhat poor knowledge of these tumours. Despite showing differentiated features, NENs exhibit therapeutic resistance to most common treatments, similar to other cancers in many instances. Molecular mechanisms responsible for this resistance phenomenon are badly understood. We aimed at identifying signalling partners responsible of acquired resistance to treatments in order to develop novel therapeutic strategies. We engineered QGP-1 cells resistant to current leading treatments, the chemotherapeutic agent oxaliplatin and the mTor inhibitor everolimus. Cells were chronically exposed to the drugs and assessed for acquired resistance by viability assay. We used microarray-based kinomics to obtain highthroughput kinase activity profiles from drug sensitive vs resistant cells and identified 'hit' kinases hyperactivated in drug-resistant cells, including kinases from FGFR family, cyclin-dependant kinases and PKCs in oxaliplatin-resistant (R-Ox) QGP-1 cells. We then validated these 'hit' kinases and observed that ERK signalling is specifically enhanced in QGP-1 R-Ox cells. Finally, we assessed drug-resistant cells sensitivity to pharmacological inhibition of 'hit' kinases or their signalling partners. We found that FGFR inhibition markedly decreased ERK signalling and cell viability in QGP-1 R-Ox cells. These results suggest that the FGFR/ERK axis is hyperactivated in response to oxaliplatin-based chemotherapeutic strategy. Thus, this sensitive approach, based on the study of kinome activity, allows identifying potential candidates involved in drug resistance in NENs and may be used to broadly investigate markers of NENs therapeutic response.